Factors affecting extent of rural livelihood diversification in selected areas of Bangladesh (SAARC Journal of Agriculture, 2018)
The study was carried out to investigate the patterns and extent of livelihood diversification in rural Bangladesh. It also identified the major factors affecting extent of livelihood diversification. The study drew a random sample of 500 rural farm households in Bangladesh through a multi-stage sampling technique. The primary data were collected using semi-structured questionnaires, and analyzed using descriptive statistics and statistical techniques. The results showed that remittance contributed the highest to the household income followed by petty business and rice farming. The estimated values of Simpson Index of Diversification (SID) showed that majority of the rural households had “medium” and “high” level diversified livelihood activities. Tobit regression analysis found that gender of the household head, household size and amount of credit had positive and significant effects; and number of migrant household member, dependency ratio, household assets, education of the household head and amount of savings had negative but significant effects on the extent of livelihood diversification. The small and medium landholding households were more likely to diversify their livelihoods compared to the functionally landless and large landholding households. The study recommended that non-farm employment opportunities should be expanded to combat poor households' vulnerability to shocks and income fluctuations. Functionally landless households should be given more attention to increase and diversify their incomes.SAARC J. Agri., 16(1): 7-21 (2018)